Production potential of different varieties of hybrid maize (Zea mays L.) with groundnut (Arachis hypogaea L.) under intercropping system - Alom, MS; Paul, NK; Quayyum, MA (Bangladesh Journal of Agricultural Research, 2010)
The experiment was carried out at the Regional Agricultural Research Station, Bangladesh Agricultural Research Institute (BARI), Jessore to evaluate the performance of different varieties of hybrid maize under intercropping systems with groundnut in Rabi seasons for higher productivity and profitability. Four sole crops of hybrid maize varieties viz., BHM-1, BHM-3, Pacific-11, and Pacific-984, one sole crop of groundnut (var. Jhingabadam) and eight intercropping systems of maize + groundnut under two planting methods viz., normal and paired row made 13 treatments, were used for two consecutive years (2004 and 2005). Treatments were arranged in a randomized complete block design with four replications. Among the intercropped treatments, four rows groundnut in between paired rows of hybrid maize var. Pacific 11 showed higher total dry mater (TDM), leaf area index (LAI), crop growth rate (CGR), gross return, net return and benefit cost ratio (BCR) than the other planting systems tested in the experiment. Keywords: Production potential; hybrid maize; groundnut; intercropping system. DOI: 10.3329/bjar.v35i1.5866 Bangladesh J. Agril. Res. 35(1) : 51-64, March 2010